TRANSLATION SHIFTS AND EQUIVALENCE STRATEGY PRODUCED BY INSTAGRAM MACHINE TRANSLATION - Antika, Ria (FKIP, UNIVERSITAS ISLAM SYEKH-YUSUF TANGERANG, 2022)
The fast advancement of technology forces people to use it to simplify their lives. In the translation field, besides human translator, there is also machine translator used to help people in transferring the meaning of a text from source language (SL) to target language (TL). Along with the development of technology and social media, Instagram as one of the most famous social media platforms launched Instagram Machine Translation in 2016 that can help people to translate the captions and comments posted by the users. This study was conducted to identify the types of translation shift and the types of translation equivalence performed by Instagram machine translation in translating the captions on @instagram account from English to Indonesian. By using descriptive qualitative method to reach the goals of the study, the appropriate data were obtained. The data were analyzed based on the translation shifts theory from Catford (1965) and translation equivalence by Nida (1964). The findings showed that all types of Catford’s translation shifts were found in the translation process and the most common type was structure shift. It was also found that Instagram machine translation was successful in transferring the message from SL to TL equivalently. Keywords: Translation shift, Translation equivalence, Instagram Machine Translation